Euphemism and Dyphemism in Position Dismissal in Tempo.co News Headline (A Language Axiology Study) - Anisa Hanifah; Dadan Rusmana (Universitas Teknokrat Indonesia, 2023)
The aim of this research is to describe alongside to analyze the meaning behind the diction of position dismissal in Tempo.co news headlines by studying euphemism and dysphemism. Judging from the language axiology study approach, the dictions that contain euphemisms and dysphemism is analyzed for their meaning and purpose. The method used in this research is a qualitative descriptive technique, to analyze the data and the quality of meaning. Then the lexical semantic method is also needed to interpret each meaning of the dictions that will be presented. The research data was collected through the technique of documenting the online news headlines of Tempo.co media. The results of this research, can describe the various types of euphemisms and dysphemism in the diction of position dismissal used by the mainstream media, by describing their meaning and purpose. The benefits of this research will be appropriate for language learners or researchers, and especially for media news readers, reporters, and editors to determine suitable framing for news headlines.